Recontextualization of the Concept of Kiai Leadership through a Distributed and Regenerative Approach for the Resilience of Islamic Boarding School Educational Institutions in the 21st Century - Nur Komariah; Jaenudin Jaenudin; Khairul Amin; Asmariani Asmariani; Irjus Indrawan (Newinera Publisher, 2025)
Centralized Kiai leadership, despite being the historical foundation of Islamic boarding schools (pesantren), faces significant challenges in addressing the complexities of the 21st century. This article discusses the recontextualization of Kiai leadership through the integration of distributed approaches and systematic regeneration to build institutional resilience. This research uses a Systematic Literature Review (SLR) following an adapted PRISMA framework. A literature search was conducted in indexed academic databases using a combination of keywords such as